WiMAX architecture for Iraq environment : mosul case study - N. Majed, Ayman (2014)
WiMAX is a broadband technology that provides an access to the internet using a wireless microwave approach which known also as Worldwide Interoperability for Microwave Access. WiMAX is a trade name that represents IEEE 802.16 standard technology which is implemented in the metropolitan area networks (MAN) level. This research is conducted because no WiMAX architecture technology have been implemented in Iraq. In this case, we need to propose a suitable WiMAX architecture that provides the most benefit out from this technology to be suitable by determining the best approach solution that will be the best choice from the all kinds that are related to this particular topic to be used in Iraq. Our methodology classified the into four phases, the Investigation phase, collecting data and analysis phase, proposing phase, evaluations and discussion phase. The Investigation phase will investigate current research in the WIMAX. Background study, problems, importance, issues in the current research in order to address gaps in WIMAX domain. In collecting data and analysis phase, we are permitted to collect and analyze the data from different sources for the sake of getting better and efficient results in our research. In proposing phase a suitable WiMAX architecture will be proposed. In order to finalize our work, the evaluations and discussion phase will take place.